DETERMINANTS FACTORS OF SKIN CARE PURCHASE DECISIONS AMONG MILLENNIALS AND GEN-Z IN MEDAN CITY - Jennifer Chandra; Varissa; Hendra Jonathan Sibarani; Debora Tambunan (International Journal of Accounting, Management, Economics and Social Sciences (IJAMESC), 2024)
Consumers today are very selective in choosing a cosmetic product until they finally make the decision to buy the product. As we know that beauty products offered are very diverse. Consumers will choose a beauty product besides having good quality, they will also choose a beauty product that is quite famous or has a brand image. The purpose of this study was to test and analyze the effect of brand image, popularity, price on purchasing decisions for skincare products for the millennial’s generation and gen-z in Medan City. This study uses quantitative research methods based on the philosophy of positivism, used to research on certain populations and samples. This study used 100 samples from the Medan Petisah sub-district whose sampling used the cluster random sampling method. Based on the research results obtained that the brand image variable has a t-statistics value of 1.398 < 1.66 and p-value of 0.163, so the brand image has no significant effect on purchasing decisions for skincare products, the brand popularity variable has a t-statistics value of 4.239 > 1.66 and p-value of 0.000, then brand popularity has a positive and significant effect on purchasing decisions for skincare products and the product price variable has a t-statistics value of 2.246 > 1.66 and p-value of 0.025, then the product price has a positive and significant effect on purchasing decisions for skincare products for millennials and gen-z in Medan City.